Determinan Harga Saham Perusahaan LQ45 Pada Bursa Efek Indonesia - I Gusti Agung Prabandari Tri Putri; Bagus Arya Wijaya; I Komang Sumerta; Ni Putu Yuliana Ria Sawitri; Gusti Ketut Amertayasa (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2022)
The purpose of this study is to determine the impact or influence of ROA, NPM and EPS on the Company's Stock Price listed in the LQ45 IDX for the 2017-2021 period. A quantitative approach is used in this study. The population includes a total of 45 LQ45 companies listed on the IDX for the 2017-2021 period. Samples were taken with a sampling target and samples from 27 companies were found. The research data were processed using multiple linear regression analysis techniques. The conclusion of the study is that partially Return on Assets has a positive impact on Stock Price, Net Profit Margin has a positive impact on stock price, and Earning Per Share has a positive impact on Stock Price. Simultaneously ROA, NPM and EPS have a significant impact on the stock price of companies listed in LQ45.